PENGARUH ANGKATAN KERJA TERHADAP KONSUMSI RUMAH TANGGA DI PROVINSI JAMBI (Periode 2016-2020) - Muchammad Hamdani (Institut Teknologi dan Bisnis Dewantara, 2021)
Regional development planning is a process carried out to determine future regional policies, through a series of options, involving various elements of stakeholders, in order to utilize and allocate resources owned by the region in a certain period of time. The 2010 Population Census noted that there were 30 ethnic groups inhabiting Jambi Province, of which 44% were from Jambi. The tribes from Jambi include the Jambi, Kerinci, Anak Dalam / Orang Rimbo, Batin / Orang Dalam, and Kubu lalan tribes.Residents, apart from being the object and subject of development, can be the basic capital in development, but they can also become obstacles or obstacles in achieving development goals. This will occur if population growth is not controlled and is not balanced with the fulfillment of needs such as clothing, food, and the need for education and health.The employment condition of Jambi Province shows a declining trend although it is not significant. There were 1,765.75 thousand people in the workforce, while around 1,691.78 people worked and 73.96 thousand people were unemployed. This shows that the unemployment rate in Jambi Province is relatively low.